2006
DOI: 10.1080/10715760600555027
|View full text |Cite
|
Sign up to set email alerts
|

In the presence of ferritin, visible light induces lipid peroxidation of the porcine photoreceptor outer segment

Abstract: We studied the synergistic effect of visible light and ferritin on the lipid peroxidation on a fraction of porcine photoreceptor outer segment (POS). Reaction mixtures containing the POS fraction and horse spleen ferritin were irradiated under white fluorescent light mainly at 17,000 lx or incubated under dark conditions at 37 degrees C. The lipid peroxidation was evaluated by both the thiobarbituric acid method and the ferrous oxidation/xylenol orange method. The irradiation-induced lipid peroxidation was aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Recent studies also suggest that in the retina cholesterol oxidation could involve ferritin, which colocalizes with 7KCh ( 9 ). Ferritin was shown to release bound iron upon light exposure ( 41 ) and induce lipid peroxidation in photoreceptor outer segments ( 42 ). This mechanism is supported by identifi cation of a new form of ferritin, mitochondrial ferritin, which localizes in the mitochondrial matrix ( 43 ).…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies also suggest that in the retina cholesterol oxidation could involve ferritin, which colocalizes with 7KCh ( 9 ). Ferritin was shown to release bound iron upon light exposure ( 41 ) and induce lipid peroxidation in photoreceptor outer segments ( 42 ). This mechanism is supported by identifi cation of a new form of ferritin, mitochondrial ferritin, which localizes in the mitochondrial matrix ( 43 ).…”
Section: Discussionmentioning
confidence: 68%
“…Other investigators have previously observed that ferritin can catalyze lipid peroxidation in bovine photoreceptors in the presence of visible light (19). Moreover, exposure of ferritin to visible light promotes release of free iron (18).…”
Section: Resultsmentioning
confidence: 96%
“…The free radical mechanism requires a transition metal catalyst (typically Fe +2 or Cu +2 ). One biologically significant form of iron is ferritin, which has been shown to enhance lipid peroxidation in photoreceptor outer segment (POS) membranes in the presence of light (18,19), and also is relatively abundant in the retina (20,21). Hence, we suspect that ferritin may be implicated in the formation of 7KCh in the retina.…”
Section: Introductionmentioning
confidence: 99%
“…Though difficult to interpret, our measurements of ftn-1 mRNA levels in hlh-29 mutants exposed to peroxide stress, support the possibility that RNAi against ftn-1 in these animals suppresses a toxic effect of excess ferritin. Recent reports in other systems show, for example, that increased ferritin levels in the presence of hydrogen peroxide [70], [71] or visible light [72] is detrimental to the cell because of increased lipid peroxidation. It is also possible that the increased sensitivity of hlh-29 ; ftn-1 (RNAi) mutants is the result of HLH-29′s influence on genes required for oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%